Analysis of Cikakembang River Water Quality Using the Pollution Index, STORET, and CCME-WQI Methods - Fitriana, Finna; Yudianto, Doddi; Seo, Yong Chan (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
River pollution is a significant environmental issue driven by urban growth and industrialization. The Cikakembang River, a tributary of the Citarum River in the Majalaya industrial area, receives wastewater from densely populated residential areas and textile manufacturing industries. Accurate assessment and monitoring of surface water quality are crucial to ensure its safe utilization. This study investigates the the Cikakembang River's water quality using the Pollution Index, STORET, and CCME-WQI methods, evaluating 14 water quality parameters across nine sampling locations during both wet and dry seasons to capture seasonal differences. The results reveal that the river fails to meet Class II water quality standards as outlined in Government Regulation No. 22 of 2021. While the Pollution Index classified contamination as mild to moderate, both STORET and CCME-WQI consistently indicated severe pollution across all sites and seasons. These findings suggest that STORET and CCME-WQI provide a more comprehensive assessment of pollution severity than the PI method, which may underestimate cumulative water quality degradation. This study highlights the urgent need for enhanced pollution control measures and stricter regulatory enforcement to mitigate further degradation of the Cikakembang River and improve its long-term sustainability.